Optimising charged Higgs boson searches at the Large Hadron Collider across bb¯W± final states - Stefano Moretti; Rui Santos; Pankaj Sharma (Physics Letters B, 2016)
In the light of the most recent data from Higgs boson searches and analyses, we re-assess the scope of the Large Hadron Collider in accessing heavy charged Higgs boson signals in bb¯W± final states, wherein the contributing channels can be H+→tb¯, hW±, HW± and AW±. We consider a 2-Higgs Doublet Model Type-II and we assume as production mode bg→tH−+c.c., the dominant one over the range MH±≥480 GeV, as dictated by b→sγ constraints. Prospects of detection are found to be significant for various Run 2 energy and luminosity options.